PREVENTION OF DENGUE HEMORRHAGIC FEVER (DHF) FOR CHILDREN IN BEKASI REGENCY: INTERACTIVE EDUCATION AND AROMATHERAPY CANDLE MAKING - Putra, Hadi Jaya; Veronica, Selly; Asyera, Erina; Aulia, Afina Nisa; P. Suradhuhita, Pratiwi; Siagian, Diandra Caroline; Adiarto, Nathania Florencia; Tambunan, Amoremio Obrianne C. (Universitas Padjadjaran, 2025)
Dengue Hemorrhagic Fever (DHF) is a serious health issue in Bekasi Regency, particularly among school-aged children. In 2024, DHF cases reached 412, with four fatalities, marking an increase compared to the previous year. This study is based on a health outreach activity consisting of two sessions: interactive education and an aromatherapy candle-making workshop. These sessions aimed to enhance children's understanding of DHF prevention. The activity was conducted in RW 12 Graha Mattel, Bekasi Regency, and involved 77 children aged 4–9 years. The interactive education methods included storytelling, games, and simulations, while the workshop taught aromatherapy candle-making using essential oils from lemongrass and lavender. The pre-test and post-test results showed a significant increase in the children's knowledge. Understanding of DHF prevention increased from 46.7% to 83.6% after the interactive education session, while understanding of the benefits and methods of making aromatherapy candles increased from 14.3% to 75.1% after the workshop. High participation in these activities underscores the success of the interactive and engaging educational approach. This study concludes that interactive learning methods and hands-on practice are effective in improving children's knowledge of DHF prevention and can be applied in other health education programs to create a healthier and more knowledgeable generation.Demam Berdarah Dengue (DBD) adalah masalah kesehatan serius di Kabupaten Bekasi, terutama di kalangan anak-anak usia sekolah. Pada tahun 2024, kasus DBD mencapai 412 dengan empat kematian, meningkat dibandingkan tahun sebelumnya. Penelitian ini didasarkan pada kegiatan sosialisasi kesehatan yang terdiri dari dua sesi, yaitu edukasi interaktif dan workshop pembuatan lilin aromaterapi. Kedua sesi ini bertujuan untuk meningkatkan pemahaman anak-anak tentang pencegahan DBD. Kegiatan ini diadakan di RW 12 Graha Mattel, Kabupaten Bekasi, dan melibatkan 77 anak-anak usia 4-9 tahun. Metode edukasi interaktif meliputi storytelling, permainan, dan simulasi, sementara workshop mengajarkan pembuatan lilin aromaterapi dengan minyak esensial serai dan lavender. Hasil pre-test dan post-test menunjukkan peningkatan signifikan dalam pengetahuan anak-anak. Pemahaman tentang penanggulangan DBD meningkat dari 46,7% menjadi 83,6% setelah sesi edukasi interaktif, dan pemahaman tentang manfaat serta cara membuat lilin aromaterapi meningkat dari 14,3% menjadi 75,1% setelah workshop. Partisipasi yang tinggi dalam kegiatan ini menegaskan keberhasilan pendekatan edukasi yang interaktif dan menarik. Penelitian ini menyimpulkan bahwa metode pembelajaran interaktif dan praktik langsung efektif dalam meningkatkan pengetahuan anak-anak tentang pencegahan DBD dan dapat diterapkan dalam program edukasi kesehatan lainnya untuk menciptakan generasi yang lebih sehat dan berpengetahuan.